NEO-SUFISM AND SOCIAL WELFARE: THE PERSPECTIVE OF INDONESIAN MUSLIM SOCIAL WORKERS - Hakim, Budi Rahman (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2025)
Abstract. Neo-Sufism, as a revitalized form of classical Sufism, offers a profound ethical and spiritual foundation that significantly enriches social welfare practices in Indonesia. This study aims to construct a theoretical framework that integrates Neo-Sufi values—such as compassion, justice, and spiritual devotion—into Muslim social work practice. Employing a qualitative literature review method, data were collected from credible academic sources indexed by Scopus and Web of Science and analyzed using thematic analysis. The findings reveal that Neo-Sufism enhances social welfare practice by providing an ethical foundation, fostering community empowerment, strengthening personal resilience among social workers, and enriching social work education curricula. These results suggest that integrating Neo-Sufi values can significantly strengthen both the professionalism and spiritual development of Muslim social workers in Indonesia, while promoting a more holistic approach to community welfare. Keyword: Neo-Sufism, Social Welfare, Muslim Social Work, Spiritual Ethics, Community Empowerment. Abstrak. Neo-Sufisme, sebagai bentuk pembaruan dari tasawuf klasik, menawarkan fondasi etis dan spiritual yang kuat untuk memperkaya praktik kesejahteraan sosial di Indonesia. Artikel ini bertujuan membangun kerangka teoretis yang mengintegrasikan nilai-nilai Neo-Sufi, seperti kasih sayang, keadilan, dan pengabdian spiritual, ke dalam praktik pekerjaan sosial Muslim. Melalui metode tinjauan pustaka kualitatif, sumber-sumber ilmiah yang terindeks Scopus dan Web of Science dianalisis menggunakan pendekatan analisis tematik. Hasil penelitian menunjukkan bahwa Neo-Sufisme memperkuat praktik kesejahteraan sosial dengan menyediakan dasar etika, meningkatkan pemberdayaan komunitas, membangun ketahanan pribadi, dan memperkaya kurikulum pendidikan sosial. Temuan ini mengindikasikan bahwa integrasi nilai-nilai spiritual Neo-Sufi dapat memperkuat profesionalisme dan meningkatkan kualitas pelayanan pekerja sosial Muslim di Indonesia, sekaligus mendorong kesejahteraan holistik masyarakat. Keyword: Neo-Sufisme, Kesejahteraan Sosial, Pekerja Sosial Muslim, Etika Spiritual, Pemberdayaan Komunitas.